The Impacts of Naked Short Selling Ban on the Stock Market of Singapore - Mirzay Fashami, Kooshan (2010)
The purpose of this dissertation is to study the impacts of naked short selling ban on the stock market of Singapore. The paper is based on the directive issued by Monetary Authority of Singapore on 22nd of September inclining the investors to refrain from practicing naked short selling. This event provides a distinctive prospect to analyze the stock market’s reaction to the new regulation. The majority of existing literature about short selling is based on two differing theories: upward bias and market completeness. Upward bias theory indicates that stock prices will bias upward in presence of short selling restrictions, whereas market completeness suggests that share prices will stay at the same level or decline due to the perceived lower efficiency of the market by investors. The study contributes to the existing literature of short selling and is particularly unique since it is the sole paper evaluating the effects of naked short selling constraints on stock market of Singapore. The research employs the event study method introduced by Brown and Warner (1985) to observe the abnormal returns during the event window. The naked short selling restrictions caused the stock prices to increase during the days close to event date and stocks observed positive abnormal return. As a result, the finding is consistent with upward bias theory. However, cumulative abnormal return of the event window is found to be substantially negative. The reason for the negative cumulative abnormal return is the contaminated period of the event. The contaminated problem can be resolved by applying Aktas et al. (2007) method to control the unrelated news.